All-inside ACL reconstruction: How does it compare to standard ACL reconstruction techniques? - Connaughton, Alexander J. (J Orthop, 2017)
The all-inside ACL reconstruction technique is a relatively new development in ACL surgery. Some features of this technique include closed-socket tunnels, dual suspensory graft fixation, decreased bone removal, and smaller skin incisions. The purpose of this review was to compare the unique features of the all-inside ACL versus standard ACL techniques using biomechanical and clinical studies. The all-inside ACL appears to have similar overall results on subjective and objective outcomes studies compared to standard ACL techniques and may be associated with decreased post-operative pain. There is also a concern for a higher graft failure rate with the all-inside ACL.